Globalization and the Asia Pacific economy - Yi, Kyŏng-tʻae (Pacific Trade and Development Conference series., 2002)
This book looks at globalization in historical perspective. It examines the experience of East Asian economies during the financial crisis, and their ambitions to modernise through deeper integration into the world economy.